The correlation between demographic processes and demoethical values of sustainable societal development in the context of climate and energy migration and water scarcity - Zhanbayev, R.A.; Maksimov, D.G.; Tansykbayeva, G.O.; Nurkenova, M.Zh.; Sagintayeva, S.S.; Sadykova, М. (Karagandy University of the name of acad. E.A. Buketov, 2023)
Object: To study the interrelation of demographic processes in the context of the most pressing global issues related to water resources, climate, energy migration, and demoethical values as a tool for the transformation of sustainable development in society. Methods: The study utilizes the concept of Demoethics, which is based on the priority of spirituality as the basis for a new stage or model of sustainable development in society, which involves integrating the demographic, socioeconomic, and ecological components into the overall processes of modeling. Findings: The proposed approach focuses on organizing activities to improve sustainable development. In particular, a demographic model is presented, which is important for the Society 5.0 and Industry 5.0 organizations. Through literature review and analysis, this research identifies key issues in the sustainable development of the demographic component of the economy based on the demoethical model and provides practical recommendations for stakeholders involved in digital transformation. Conclusions: In order to achieve the Sustainable Development Goals (SDG) for countries, civil society, and international institutions by 2030, commitments have been made to accomplish a range of tasks, from reducing extreme poverty to ensuring environmental sustainability and universal education, reducing child mortality, and promoting gender equality. Despite the fact that adaptation activities directly contribute to achieving SDG 13, which focuses on taking action against climate change, it should be seen as part of a strategy to strengthen a country's achievements in implementingall other SDGs based on the value of Demoethics. Expected results: The results of this study can serve as a basis for supporting targeted policies and the transformation of demographic components of the economy.
Климаттық және энергетикалық көші–қон және су тапшылығы контексіндегі демографиялық процестердің демоэтикалық құндылықтарымен қоғамның тұрақты даму байланысы
Взаимосвязь демографических процессов с демоэтическими ценностями устойчивого развития общества в контексте климатической и энергетической миграции и нехватки воды
Keywords: sustainable development goals (SDG); sustainable development; demoethics values; climate migration; energy migration; Central Asia’s security; water resources; quality of life; transformation